Public Participation in Foreign Policy
XVII, 259 p.
Keywords: Experts from academia, governments, think tanks, NGOs, trade unions, and business investigate whether the public should play a greater role in foreign policy making by analysing their current role in the Iraq war (USA), Post-Apartheid (South Africa), trade relations with China (New Zealand) and other cases.